OPTIMALISASI UKURAN BLEED TERHADAP JUMLAH KATERN RUSAK DAN KEBUTUHAN KERTAS - Anugerah Putera Nureko; Endang Yuniarti; HB. Rudi Kusumantoro (Politeknik Negeri Jakarta, 2022)
The use of bleed size in the book production process greatly affects the quality of the product. Bleed size serves as a measure of tolerance given when placing the book layout on 1 sheet of katern so that the size of the finished product is met. Reducing the size of the bleed will result in the resulting page fold (katern) being rejected. However, if the size of the bleed is too large, it will result in high paper costs. This will also result in losses for the company. The aim of this research is to get the optimal bleed size that produces the least reject products. The results showed that the optimal size of the bleed on matt paper (120 gsm) paper was 8 mm. Because this measure produces the least amount of damaged material that is close to the standard, namely 20% of the production circulation. The paper requirement for 8 mm bleed is 18.92 reams or 635.3 kg with a paper size of 61x92 cm.